Cardiac Glycoside Ouabain Exerts Anticancer Activity via Downregulation of STAT3 - Du, Jie; Jiang, Lijun; Chen, Fuqiang; Hu, Huantao; Zhou, Meijuan (Frontiers in Oncology, 2021)
Cardiac glycosides are plant-derived steroid-like compounds which have been used for the treatment of cardiovascular diseases. Ouabain, a cardiotonic steroid and specific Na+/K+-ATPase inhibitor, has been rediscovered for its potential use in the treatment of cancer. However, the cellular targets and anticancer mechanism of ouabain in various cancers remain largely unexplored. In this study, we confirmed the cytotoxic effects of ouabain on several cancer cell lines. Further examination revealed the increase of apoptosis, intracellular ROS generation and DNA double-strand breaks induced by ouabain treatment. Besides, ouabain effectively suppressed STAT3 expression as well as phosphorylation in addition to block STAT3-mediated transcription and downstream target proteins. Interestingly, these inhibitory activities seemed to be independent of the Na+/K+-ATPase. Furthermore, we found that ouabain inhibited protein synthesis through regulation of the eukaryotic initiation factor 4E (eIF4E) and eIF4E binding protein 1 (4EBP1). Taken together, our study provided a novel molecular insight of anticancer activities of ouabain in human cancer cells, which could raise the hope of using cardiac glycosides for cancer therapeutics more rational.